Development and Psychometric Properties of a Scale of Teachers’ Coping Strategies Towards the Evaluation of Performance in Public Schools - Jocabeth Nohemi Chambilla-Apaza; Ailyn Yicela Merchan-Fuentes; Denis Frank Cunza-Aranzábal; Carlos D. Abanto-Ramírez (Education Sciences)
Teaching evaluation performance is an important policy adopted by the governing body of education in Peru to promote the growth of educational quality, professional development, and continuous training of teachers, as well as to ensure educational quality standards, especially in Peruvian elementary education. Therefore, this research aims to develop and evaluate the psychometric properties of a scale that measures the coping strategies adopted by elementary education teachers when evaluating their performance. A study was conducted with 317 teachers between 20 and 70 years old (M = 43.6, SD = 11.8) in public education, from preschool (10.4%) to secondary (24.9%) educational levels, including special and alternative education, and with employment status of contracted (46.1%) and appointed (53.9%). An exploratory factor analysis was performed, from which four factors emerged. These factors were then corroborated by confirmatory factor analysis (χ2 = 162, df = 13, CFI = 0.968, TLI = 0.961, RMSEA = 0.061, and SRMR = 0.056) and were named as follows: maladaptive coping, adaptive individual coping, religious coping, and instrumental support coping. Internal reliability was high for the full scale and dimensions (α and ω > 0.8), indicating that it was free of random error, yielding the same results across multiple applications for the same sample. It is concluded that the scale of teachers’ coping strategies towards the evaluation of performance (STCEP) is a valid and reliable instrument to measure coping strategies adopted by elementary education teachers in response to performance evaluation.